Hybrid Recursive Active Filters for Duplexing in RF Transmitter Front-Ends - Gottardo, Giuseppe; Donati, Giovanni; Musolff, Christian; Fischer, Georg; Felgentreff, Tilman (Mediterranean Microwave Symposium, 2015)
Duplex filters in modern base stations are designed as cavity filters, which are expensive and have big dimensions. Thanks to the emerging digital technology and fast digital converters, it is possible to transfer the efforts of designing analog duplex filters into digital numeric algorithms applied to feedback structures, operating on power amplifiers in transmitters. The design of a digital baseband feedback applied to the analog power RF amplifiers (hybrid filter) is presented and verified by measurements. The use of multiple digital feedback branches allows the closed loop system to show a periodic band-pass behavior at the output of the RF amplifier with a larger bandwidth up to 500 KHz. Moreover the band pass magnitude reaches up to 17 dB difference between maximum gain and attenuation.
elib2cris::1512001600,gottardo2015a
Keywords: active filter; feedback amplifier; base station; stability analysis; interference suppression; band-pass filters; cavity resonators

Hybrid Recursive Active Filters for Duplexing in RF Transmitter Front-Ends - Gottardo, Giuseppe; Donati, Giovanni; Musolff, Christian; Fischer, Georg; Felgentreff, Tilman (Radio Science, 2016)
Duplex filters in modern base transceiver stations (BTS) provides the channel shape in order to perform common frequency division duplex (FDD) operation. Usually they are designed as cavity filters, which are expensive and have big dimensions. Thanks to the emerging digital technology and fast digital converters, it is possible to transfer the efforts of designing analog duplex filters into digital numeric algorithms applied to feedback structures, operating on power amplifiers in transmitters. This solution provides the shaping of the signal spectrum directly at the output of the radio frequency (RF) power amplifiers (PAs) relaxing the transmitter design especially in the duplexer and the antenna sections. The design of a digital baseband feedback applied to the analog power RF amplifiers (hybrid filter) is presented and verified by measurements. A model to describe the hybrid system is investigated and the relation between phase and resonance peaks in the resulting periodic band-pass transfer function is described. The stability condition of the system is analyzed using Nyquist criterion and defining a safe work region in order to avoid oscillation. A solution involving a number of digital feedback and forward branches is investigated defining recursive structure parameters of the hybrid filter. This last solution allows the closed loop system to show at the output of the RF amplifier a periodic band-pass with up to 500 KHz bandwidth. Moreover, the band-pass magnitude reaches up to 17 dB difference between maximum gain and attenuation.
elib2cris::1512001600,gottardo2016
Keywords: active filter; feedback amplifier; base station; stability analysis; interference suppression; band-pass filters

Hybrid Recursive Active Filters for Frequency Agile Architectures - Gottardo, Giuseppe (COMORA, Cognitive Mobile Radio Workshop - Kognitive Drahtlose Kommunikationssysteme Abschluss Workshop, 2014)
elib2cris::1512001600,gottardo2014a
Keywords: Active filter; feedback amplifier; base station; stability analysis; interference suppression; feedback amplifier; cavity resonators

Hybrid Recursive Active Filters for High Selectivity in RF Transmitter Front-Ends - Gottardo, Giuseppe; Donati, Giovanni; Musolff, Christian; Fischer, Georg; Felgentreff, Tilman (2nd International Scientific Symposium ”Sense. Enable. SPITSE.” 2015, 2015)
Duplex filters in modern base stations are designed as cavity filters, which are expensive and have big dimensions. Thanks to the emerging digital technology and fast digital converters, it is possible to transfer the efforts of designing analog duplex filters into digital numeric algorithms applied to feedback structures, operating on power amplifiers in transmitters. The design of a digital baseband feedback applied to the analog power amplifiers is described making use of a model here verified by measurements. The design of hybrid filters allows the closed loop system to reach up to 20 dB difference between maximum gain and attenuation. Particular attention is dedicated to preserve stability conditions. The proposed architecture has the potential to reduce the cost and size of the RF front-ends.
elib2cris::1512001600,gottardo2015
Keywords: Active filter; feedback amplifier; base station; stability analysis; interference suppression; band-pass filters; cavity resonators

Novel Hybrid Recursive Active Filters in RF Transmitter Front-Ends - Gottardo, Giuseppe; Donati, Giovanni; Musolff, Christian; Weigel, Robert; Fischer, Georg (German Microwave Conference, 2014)
Duplex filters in modern base stations are designed as cavity filters, which are expensive and have big dimensions. In order to reduce the size of these filters a novel hybrid system using a power amplifier and a negative digital feedback for frequency band GSM900 is studied. A model to describe the hybrid system is investigated and the relation between phase and resonance peaks in the transfer function is described. An attenuation of 5.4 dB for the closed loop transfer function is reached. The stability condition of the system is here presented using Nyquist criterion as an important step for its future feasibility.
elib2cris::1512001600,gottardo2014
Keywords: Active filter; feedback amplifier; base station; stability analysis; interference suppression; band-pass filters; cavity resonators

Physically inspired digital predistortion for doherty power ampliers and automatic in-situ identication - Donati, Giovanni; Musolff, Christian; Gottardo, Giuseppe; Popp, Daniel; Fischer, Georg (Fifth International Conference on Telecommunications and Remote Sensing, 2016)